THE LEADERSHIP CHALLENGE WORKBOOK - Kouzes, James M., 1945-, author; Posner, Barry Z., author (San Francisco, CA : The Leadership Challenge, 2017)
Essential, practical tools for implementing evidence-based leadership development The Leadership Challenge Workbook offers practical tools for applying The Five Practices of Exemplary Leadership(R) in real-life business situations